Anticoagulation use and the risk of stroke and major bleeding in patients on hemodialysis: From the VIVALDI, a population‐based prospective cohort study. (5th September 2021) - Königsbrügge, Oliver; Meisel, Hannah; Beyer, Aljoscha; Schmaldienst, Sabine; Klauser‐Braun, Renate; Lorenz, Matthias; Auinger, Martin; Kletzmayr, Josef; Hecking, Manfred; Winkelmayer, Wolfgang C.; Lang, Irene; Pabinger, Ingrid; et al.
Abstract: Background: Evidence supporting the use of anticoagulation for the prevention of stroke and thromboembolism in patients with kidney failure on hemodialysis (HD) and atrial fibrillation (AF) is limited. We prospectively assessed the incidences of stroke and major bleeding, as well as anticoagulation strategies in patients on HD with AF. Methods: We recruited 625 prevalent HD patients into a population‐based observational cohort study. The primary prospective outcomes were thromboembolic events (stroke, transient ischemic attack, systemic embolism) and major bleeding. Secondary outcomes included a composite of thromboembolic events, major bleeding, and cardiovascular death to determine net clinical harm. Results: A total of 238 patients (38.1%) had AF, 165 (26.4%) already at baseline and 73 (15.9%) developed AF during a median follow up of 870 days. Forty (6.4%) thromboembolic events and 89 (14.2%) major bleedings occurred. Overall, 256 patients died (41.0%). In AF patients, use of vitamin K antagonists (VKAs) in 61 patients (25.6%) was not significantly associated with reduced risk of the primary thromboembolic outcome (subdistribution hazard ratio [SHR] 1.41 adjusted for age, sex, congestive heart failure, hypertension, stroke/transient ischemic attack/thromboembolism, vascular disease, and diabetes history score and antiplatelet co‐medication (95% CI, 0.49–4.07), but with increased risk of major bleeding (SHR: 2.28; 95% CI, 1.09–4.79) compared with AF patients without anticoagulation ( N  = 139, 58.4%). Use of VKAs was associated with net clinical harm (adjusted SHR: 2.07; 95% CI, 1.25–3.42). Conclusions: Although the nonrandomized nature of the study is prone to bias, anticoagulation with VKAs was not associated with decreased thromboembolic risk, but rather with increased risk of major bleeding and may be net harmful to patients with AF on HD.